Long term sertraline effects on neural structures in depressed and nondepressed adult female nonhuman primates. (December 2015) - Willard, Stephanie L.; Uberseder, Beth; Clark, Ashlee; Daunais, James B.; Johnston, Warwick D.; Neely, David; Massey, Adreanna; Williamson, Jeff D.; Kraft, Robert A.; Bourland, J. Daniel; Jones, Sara R.; Shively, Carol A.
Abstract: Background: Selective serotonin reuptake inhibitors (SSRIs) are widely prescribed for mood and other disorders. However, their neural effects are difficult to study due to patient compliance and drug history variability, and rarely studied in those prescribed SSRIs for non-mood disorders. Here we evaluated SSRI effects on neural volumetrics in depressed and nondepressed monkeys. Methods: 42 socially-housed cynomolgus monkeys were randomized to treatment balanced on pretreatment depressive behavior and body weight. Monkeys were trained for oral administration of placebo or 20 mg/kg sertraline HCl daily for 18 months and depressive and anxious behavior recorded. Volumes of neural regions of interest in depression were measured in magnetic resonance images and analyzed by 2 (depressed, nondepressed) × 2 (placebo, sertraline) ANOVA. Results: Sertraline reduced anxiety (p = 0.04) but not depressive behavior (p = 0.43). Left Brodmann's Area (BA) 32 was smaller in depressed than nondepressed monkeys (main effect of depression: p < 0.05). Sertraline and depression status interacted to affect volumes of left Anterior Cingulate Cortex (ACC), left BA24, right hippocampus (HC), and right anterior HC (sertraline × depression interactions: all p's < 0.05). In the Placebo group, depressed monkeys had smaller right anterior HC and left ACC than nondepressed monkeys. In nondepressed monkeys, sertraline reduced right HC volume, especially right anterior HC volume. In depressed monkeys sertraline increased left ACC volume. In nondepressed monkeys, sertraline reduced left BA24 volumes resulting in smaller BA24 volumes in nondepressed than sertraline-treated depressed monkeys. Conclusions: These observations suggest that SSRIs may differentially affect neural structures in depressed and nondepressed individuals. Highlights: SSRI effects on neuroanatomy were evaluated in depressed and nondepressed monkeys. SSRIs reduced anxiety but did not affect depression. Neural areas associated with human depression were smaller in depressed monkeys. SSRIs differentially affected neural volumes in depressed vs. nondepressed monkeys. Anterior cingulate & hippocampal areas were smallest in SSRI-treated nondepressed.